2020
DOI: 10.3389/fgene.2020.589326
|View full text |Cite
|
Sign up to set email alerts
|

Temporospatial Flavonoids Metabolism Variation in Ginkgo biloba Leaves

Abstract: Ginkgo (Ginkgo biloba L.) is a high-value medicinal tree species characterized by its flavonoids beneficial effects that are abundant in leaves. We performed a temporospatial comprehensive transcriptome and metabolome dynamics analyses of clonally propagated Ginkgo plants at four developmental stages (time: May to August) across three different environments (space) to unravel leaves flavonoids biosynthesis variation. Principal component analysis revealed clear gene expression separation across samples from dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Flavonoids are important compounds closely related to the color of plant organs. Recent studies have also found that flavonoids can regulate key enzymes, participate in antioxidant defense, have antimicrobial activity, and increase plant biological and abiotic stress resistance [ 72 , 73 , 74 ]. In particular, flavonoids can scavenge oxygen free radicals produced in plants, known as reactive oxygen species (ROS) [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are important compounds closely related to the color of plant organs. Recent studies have also found that flavonoids can regulate key enzymes, participate in antioxidant defense, have antimicrobial activity, and increase plant biological and abiotic stress resistance [ 72 , 73 , 74 ]. In particular, flavonoids can scavenge oxygen free radicals produced in plants, known as reactive oxygen species (ROS) [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing data were processed using Trimmomatic, differentially expressed genes (DEGs) were identified using DESeq R package functions estimate size factors and nbinom test, and enrichment(GO and KEGG pathway);was performed based on the hypergeometric distribution ( 24 ). In addition, the DEGs expression pattern was visualized and analyzed by Short Time-series Expression Miner (STEM) software ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“… 80 , 81 GbbHLH, GbTrihelix , and three GbERFs contributed to flavonoid biosynthesis by regulating the expression of structural genes in the flavonoid biosynthesis pathway. 82 In recent years, some studies found that TCPs may also be involved in flavonoid biosynthesis. For instance, AtTCP15 affected anthocyanin accumulation by inhibiting the expression of anthocyanin biosynthesis genes, 38 and FvTCP9 promoted anthocyanin accumulation by affecting the expression of genes involved in the ABA signal transduction pathway.…”
Section: Candidate Gbtcps Involved In Flavonoids B...mentioning
confidence: 99%